Towards a Post-Anthropocentric Speculative Archaeology (through Design). (2nd February 2018) - Ståhl, Ola; Tham, Mathilda; Holtorf, Cornelius
Abstract : As disciplines and practices archaeology and design stand in an interesting relationship to one another. Whereas it is the business of designers to construct material and, at times, immaterial universes that can sustain life (or, as we shall see, destroy life), it is the business of archaeologists, in the traditional sense of the word, to look at the remnants of those universes and the traces of those who populated them in order to understand the past and the ways in which it resonates in the present and in our conception of our possible futures. This leads us to pose the following question: If an intimate relationship can be located at the interstitial space between archaeology and design, what might happen if we were to construct transversal lines between and across these disciplines, and what concepts would be required for us to do so? Drawing upon the concept of the Anthropocene – a concept opening up to precisely such transdisciplinary and transversal approaches – this article explores the notion of a post-anthropocentric speculative archaeology interweaving a theoretical line of thought and a performative, fictive trajectory.